THE EFFECT OF DIFFERENT TEMPERATURES ON THE ANTIBACTERIA EFFECTIVENESS OF BROWN SEAWEED EXTRACT (Sargasum plagyophyllum) TOWARD Staphylococcus aureus AND Pseudomonas aeruginoosa - Dinda Futhi Khumaira; N. Ira Sari; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aimed to determine the effect of different temperatures on the effectiveness of brown seaweed extract (Sargasum plagyophyllum) as an antibacterial agents for Staphylococcus aureus and Pseudomonas aeruginoosa. The treatment conducted was heating the extract with  varied temperatures (50, 60 and 70 ºC). The parameters assessed were the clear zone diameter on each medium for Staphylococcus aureus and Pseudomonas aeruginosa bacteria. The results showed that the extracting the brown seaweed at the temperature of 70 ºC was the most effective treatment to inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa bacteria with an inhibition zone diameter of 4.31 mm of 8.30 mm, respectively. Keywords: Antibacterial, Pseudomonas aeruginoosa, Sargasum plagyophyllum and Staphylococcus aureus